Beta diversity of stream insects differs between boreal and subtropical regions, but land use does not generally cause biotic homogenization - Petsch, Danielle K.; Saito, Victor S.; Landeiro, Victor L.; Silva, Thiago S. F.; Bini, Luis M.; Heino, Jani; Soininen, Janne; Tolonen, Kimmo T.; Jyrkänkallio-Mikkola, Jenny; Pajunen, Virpi; Siqueira, Tadeu [UNESP]; Melo, Adriano S. (University of Chicago Press, 2021)
Previous studies have found mixed results regarding the relationship between beta diversity and latitude. In addition, by influencing local environmental heterogeneity, land use maymodify spatial taxonomic and functional variability among communities causing biotic differentiation or homogenization. We tested 1) whether taxonomic and functional beta diversities among streams within watersheds differ between subtropical and boreal regions and 2) whether land use is related to taxonomic and functional beta diversities in both regions.Wesampled aquatic insects in 100 subtropical (Brazil) and 100 boreal (Finland) streams across a wide gradient of land use, including agriculture and exotic planted, secondary, and native forests.We calculated beta diversity at thewatershed scale (among 5 streams in each watershed).We found higher taxonomic beta diversity among subtropical than among boreal streams,whereas functional beta diversity was similar between the 2 regions. Total land use was positively correlated with taxonomic and functional beta diversity among subtropical streams, while local environmental heterogeneity was positively correlated with beta diversity among boreal streams. We suggest that different types and intensities of land use may increase among-streamheterogeneity, promoting distinct insect assemblage compositions among streams. Our findings also suggest that beta diversity patterns and their underlying determinants are highly context dependent.
Keywords: Aquatic insects; Biological traits; Environmental heterogeneity; Functional homogenization; Latitudinal diversity gradient